Shareholder protection and bank executive compensation after the global financial crisis - Abascal, Ramón; González, Francisco (Journal of Financial Stability, 2019)
We use a hand-collected international database to analyze the change in the risk-taking incentives embedded in bank executive compensation after the onset of the global financial crisis. Our results reveal a reduction in both the risk sensitivity of stock option grants (vega) and total and cash pay-risk sensitivities in countries suffering systemic banking crises. This reduction is greater in countries with strong shareholder protection, especially in banks with good corporate governance, solvent banks, and banks that suffered a reduction in their specific investment opportunity set. The regressions control for government intervention, banking development, and crisis intensity. Our results confirm that the contracting hypothesis is more relevant in countries with stronger shareholder protection, and provide support for measures improving shareholder rights in the approval of bank executive compensation.